Sur certains résultats ayant comme point de départ le programme de recherche de l'Institut de Calcul de Cluj-Napoca de l'Académie Roumaine: On some results starting from the research program of the Institute of Numerical Analysis of Cluj-Napoca of the Romanian Academy - Popoviciu, Elena (Rev. Anal. Numér. Théor. Approx., 1999)
Not available.